CHANGES IN EFFORT TOLERANCE INDICES IN PATIENTS WITH CHRONIC HEART FAILURE AND LATENT IRON DEFICIENCY ON THE BACKGROUND OF THE ORAL FERROTHERAPY - Ivanov, V.P.; Kolesnyk, M.O.; Kolesnуk, O.M.; Bilonko, O.F.; Nіushko, T.Y. (World of Medicine and Biology, 2020)
It is known that iron deficiency (ID) in the case of chronic heart failure (CHF), regardless of the presence of anemia, contributes to the development of the skeletal muscle dysfunction, which results in a reduction of effort tolerance (ET) in patients. The objective of the study was to assess the changes in effort tolerance indices in patients with chronic heart failure, with reduced left ventricular ejection fraction and concomitant latent iron deficiency, on the background of a standard treatment combined with long-term oral ferrotherapy. The data obtained showed that the conducted additional oral ferrotherapy is accompanied by a substantial improvement in effort tolerance indices in patients with CHF as compared to the standard therapy alone. This demonstrates the feasibility of a latent ID 6-month oral ferrocorrection to treat CHF with reduced LV EF in order to improve the patients’ condition and working capacity.
Keywords: chronic heart failure; latent iron deficiency; oral ferrotherapy